2022
DOI: 10.3390/molecules27062008
|View full text |Cite
|
Sign up to set email alerts
|

Plants Used in Mexican Traditional Medicine for the Management of Urolithiasis: A Review of Preclinical Evidence, Bioactive Compounds, and Molecular Mechanisms

Abstract: Urolithiasis (UL) involves the formation of stones in different parts of the urinary tract. UL is a health problem, and its prevalence has increased considerably in developing countries. Several regions use plants in traditional medicine as an alternative in the treatment or prevention of UL. Mexico has known about the role of traditional medicine in the management of urinary stones. Mexican traditional medicine uses plants such as Argemone mexicana L., Berberis trifoliata Hartw. ex Lindl., Costus mexicanus Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
1
5
0
1
Order By: Relevance
“…It is estimated that more than 90% of Mexicans use preparations based on medicinal plants due to the ancestral knowledge developed through time. 81 As compiled in Table 3, Mexican medicinal plants can decrease the viability of breast, lung, colorectal, oropharyngeal, and hepatocellular cancer cell lines by fragmenting DNA, enhancing the generation of ROS, promoting apoptosis, upregulating or downregulating gene expression, interfering with cell cycle phases, and inducing morphological changes. Interestingly, we identified that in multiple reports, these events are predominantly promoted in vitro or in vivo with extracts prepared with mildly polar to polar solvents such as ethyl acetate and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that more than 90% of Mexicans use preparations based on medicinal plants due to the ancestral knowledge developed through time. 81 As compiled in Table 3, Mexican medicinal plants can decrease the viability of breast, lung, colorectal, oropharyngeal, and hepatocellular cancer cell lines by fragmenting DNA, enhancing the generation of ROS, promoting apoptosis, upregulating or downregulating gene expression, interfering with cell cycle phases, and inducing morphological changes. Interestingly, we identified that in multiple reports, these events are predominantly promoted in vitro or in vivo with extracts prepared with mildly polar to polar solvents such as ethyl acetate and ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…Standard medications used for the prevention and treatment of urolithiasis, such as uricosuric, diuretic, and hypoazotemic agents, do not always show universal effectiveness and may cause side effects [ 41 ]. Recent experimental and clinical studies have confirmed that biologically active compounds, such as flavonoids, phenolic acids, phytosterols, saponins, furanochromones, alkaloids, and terpenoids can effectively suppress the formation of calcium-oxalate urinary calculi (the most common kidney stones) [ [41] , [42] , [43] ]. These compounds found in the chemical composition of various plants, demonstrate litholytic, lithokinetic, antispasmodic, diuretic, antimicrobial, antioxidant, and anti-inflammatory properties [ 43 , 44 ], which can inhibit lithogenesis in the urinary system, and in particular, the processes of crystallization, nucleation and aggregation of crystals [ 44 , 45 ].…”
Section: Antiurolytic Actionmentioning
confidence: 99%
“…Recent experimental and clinical studies have confirmed that biologically active compounds, such as flavonoids, phenolic acids, phytosterols, saponins, furanochromones, alkaloids, and terpenoids can effectively suppress the formation of calcium-oxalate urinary calculi (the most common kidney stones) [ [41] , [42] , [43] ]. These compounds found in the chemical composition of various plants, demonstrate litholytic, lithokinetic, antispasmodic, diuretic, antimicrobial, antioxidant, and anti-inflammatory properties [ 43 , 44 ], which can inhibit lithogenesis in the urinary system, and in particular, the processes of crystallization, nucleation and aggregation of crystals [ 44 , 45 ]. Based on their systematic review of 163 original articles retrieved from the PubMed database, A. Khan et al concluded that the antiurolytic effect of herbal preparations stems from their antioxidant, anti-inflammatory, and/or diuretic effects [ 46 ].…”
Section: Antiurolytic Actionmentioning
confidence: 99%
“…Evidence points to their potential litholytic, antispasmodic, and diuretic properties as well as an inhibitory influence on crystallization, nucleation, and aggregation of crystals as the possible causes of their therapeutic effects. These benefits may be caused by antioxidant, anti-inflammatory, or antibacterial characteristics, according to the molecular pathways involved [5]. This chapter summarizes the role bioactive compounds and mechanisms of medicinal plants in the treatment of nephrolithiasis.…”
Section: Introductionmentioning
confidence: 99%